Development of Dangerous Object Detection for Security Application in Video Surveillance System - Mohd Zubir, Azhani (IRC, 2019)
Video surveillance system such as Closed Circuit Television (CCTV) helps to monitor the situation in public places. This is to ensure the security of the general public and safety of public assets are protected. Often times, crime activities such as attacks and terrorism occurs at public places which can cause potential harm to the public. Thus, it is important to have a surveillance system that can detect individuals that possess dangerous objects within them. Dangerous object or weapon can be defined as a device used by an individual to conflict harm on other individual or group.